2014
DOI: 10.1073/pnas.1313368111
|View full text |Cite
|
Sign up to set email alerts
|

High throughput 3D super-resolution microscopy reveals Caulobacter crescentus in vivo Z-ring organization

Abstract: We created a high-throughput modality of photoactivated localization microscopy (PALM) that enables automated 3D PALM imaging of hundreds of synchronized bacteria during all stages of the cell cycle. We used high-throughput PALM to investigate the nanoscale organization of the bacterial cell division protein FtsZ in live Caulobacter crescentus. We observed that FtsZ predominantly localizes as a patchy midcell band, and only rarely as a continuous ring, supporting a model of "Z-ring" organization whereby FtsZ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
194
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(226 citation statements)
references
References 31 publications
(38 reference statements)
23
194
3
Order By: Relevance
“…The combined mean Z-ring width (along the cell long axis) of 99 ± 3 nm (n = 168; Fig. 1C) is consistent with previous measurements of 60-120 nm in E. coli (19,48,59) and Caulobacter crescentus (53,60). Note that dimension measurements reported here have been deconvolved from the achieved resolution to facilitate comparison across different experiments (61) (Materials and Methods); see SI Appendix, Table S1 for apparent dimensions before deconvolution.…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…The combined mean Z-ring width (along the cell long axis) of 99 ± 3 nm (n = 168; Fig. 1C) is consistent with previous measurements of 60-120 nm in E. coli (19,48,59) and Caulobacter crescentus (53,60). Note that dimension measurements reported here have been deconvolved from the achieved resolution to facilitate comparison across different experiments (61) (Materials and Methods); see SI Appendix, Table S1 for apparent dimensions before deconvolution.…”
Section: Resultssupporting
confidence: 86%
“…We showed that the Z-ring is not a smooth structure but instead comprises clusters of FtsZ protofilaments that loosely associate into a 3D bundle (19,48). This heterogeneous morphology has also been observed with several different fluorescent protein tags (19), in different bacterial species (51)(52)(53)(54), by immuno-superresolution imaging targeting native FtsZ (19,54), by superresolution imaging of FtsZ-binding proteins (19,54), and in an early electron cryotomography (ECT) study (37). Here, we further demonstrate that an FtsZ-GFP fusion colocalizes with native FtsZ in midcell clusters in two-color superresolution imaging using antibodies against native FtsZ and GFP (SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…For this study, to ensure that each software was properly tuned to our simulated database, npg we encouraged the developers themselves to run their own software, guided by the training data. To alleviate the difficulty of presetting parameters, we suggest that developers incorporate self-calibration capabilities or dynamically tune the parameters 26 . We predict that this will be one of the key factors determining the success of future software 14 .…”
Section: Discussionmentioning
confidence: 99%
“…up of loosely arranged irregular patches of protofilaments, which gives it an overall discontinuous structure (Li et al 2007, Holden et al 2014. Following studies using highresolution fluorescence microscopy techniques revealed that such was the case in many other bacterial species (Strauss et al 2012, Rowlett & Margolin 2014, Jacq et al 2015.…”
Section: :9mentioning
confidence: 97%